Children's food intake in relation to preschool-level facilitators and barriers of healthy nutrition. (13th November 2019) - Lehto, R; Ray, C; Vepsäläinen, H; Korkalo, L; Nissinen, K; Koivusilta, L; Roos, E; Erkkola, M
Abstract: Background: Childcare is an important setting for young children's food consumption as, in Finland, most children eat three meals a day in childcare. Thus, it is important to recognize determinants of children's dietary intake in childcare. The aim of this study was to examine food-related factors at preschool and manager-level and their association with children's fruit, vegetable and fibre intake at preschool. Methods: The study was a part of the cross-sectional DAGIS survey conducted in 2015-2016. It aimed to examine 3-6-year-old preschoolers' energy balance-related behaviors in Finland. Preschool managers from 58 preschools filled in a questionnaire on food and nutrition related factors at preschool such as kitchen type, food policies, food education, the manager's possibilities to impact fruit and vegetable supply and cooperation challenges with the catering service. Preschool personnel kept food record for the children (n = 585) on two preschool days. Multilevel linear and logistic regression analyses were conducted with age, gender and municipality as confounders, preschool-level factors as independent variables and children's vegetable (g/day) and fruit (yes vs. no) consumption, and fibre intake (g/MJ) as outcome variables. Results: Having many written food policies in the preschool was associated with higher intake of vegetables (p = 0.01) and fibre (p = 0.03) among the children. Having at least 2 out of 3 different cooperation challenges with the catering service was associated with higher intake of fibre (0.03) and lower odds of eating fruits (p = 0.01). Conclusions: Written food policies and manager-reported challenges with the catering service were associated with children's vegetable, fruit and fiber intake at preschool. Factors that are relatively distal from the meal situations may impact children's food intake at preschool and should be taken into account when promoting healthy food intake at preschool, but more studies are needed. Key messages: Written food policies and good cooperation between the preschool and catering services may be of benefit to children's healthy food intake at preschool. The relation between preschool and manager-level factors and children's food intake are very little studied, and thus more studies are needed before conclusions can be made.